Analysis of the Effect of Unemployment Rate, RMW, and HDI on Poverty Rates in the Special Region of Yogyakarta - Yolanda Oktaviani; Indanazulfa Qurrota A'yun (Journal of Economics Research and Social Sciences, 2021)
Poverty is one of the most complex problems in a country's economy, including in a region. Therefore, efforts to reduce poverty must be carried out comprehensively. The purpose of this study was to analyze the effect of the unemployment rate, the Regional Minimum Wage (RMW), and the Human Development Index (IPM) on the poverty rate in the districts of Bantul, Sleman, Gunung Kidul, Kulon Progo, and the City of Yogyakarta in 2015-2019. The analytical method used is panel data regression random effect models (REM). This study indicates that the unemployment rate, regional minimum wage, and HDI simultaneously affect the poverty level. Partially, the unemployment rate is positively and not significantly correlated with the poverty rate.